2012
DOI: 10.1177/1474515111435608
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative education and counselling are associated with reduced anxiety symptoms following carotid endarterectomy: a randomized and open-label study

Abstract: Pre-operative visits and counselling by ICU nurses could reduce patient's anxiety levels following carotid endarterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 13 publications
1
17
0
4
Order By: Relevance
“…This study found a significant difference in anxiety and depressive symptoms scores between the intervention and the control group. The current findings are consistent with those of a previous study in which 120 patients undergoing carotid endarterectomy (an invasive procedure) were randomized to receive structured information and counseling the day before surgery or standard preintervention counseling [24]. Adequate information regarding the procedure and counseling effectively reduced the level of anxiety.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study found a significant difference in anxiety and depressive symptoms scores between the intervention and the control group. The current findings are consistent with those of a previous study in which 120 patients undergoing carotid endarterectomy (an invasive procedure) were randomized to receive structured information and counseling the day before surgery or standard preintervention counseling [24]. Adequate information regarding the procedure and counseling effectively reduced the level of anxiety.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, we offered a single education and counseling session. However, several studies have shown that brief counseling appeared as effective in reducing anxiety as longer treatments [24, 3840]. Notwithstanding, further research with longer duration of education and counseling, together with a cost effectiveness analysis, may be needed to better elucidate the effect of information and counseling for reducing anxiety in women undergoing HSG.…”
Section: Discussionmentioning
confidence: 99%
“…The September issue of the European Journal of Cardio vascular Nursing was focused entirely on psychosocial topics, with papers addressing depression and anxiety [1][2][3][4] ; coping 5 ; quality of life 1,[6][7][8] ; personality 7,9 ; and psychological adjustment. 10 Since psychosocial consequences of cardiac disease and treatment are so important, this previous issue of the journal formed a timely and much needed collection of articles.…”
mentioning
confidence: 99%
“…The importance and efficacy of preoperative counseling has been similarly signified by previous trials on various ethnic groups. [1213] This study highlights the augmented anxiolytic effect with flupirtine reflected as lower VAS scores of various anxiety variables, measured on the evening before surgery.…”
Section: Discussionmentioning
confidence: 79%